Prevalence Of Potentially Inappropriate Medication In The Older Adult Population Within Primary Care In Portugal: A Nationwide Cross-Sectional Study - Simões, Pedro Augusto Gomes Rodrigues Marques (2019)
Background: In potentially inappropriate medications harm potentially outweighs benefits. Even appropriately prescribed medications may become inappropriate. They can lead to a high risk of adverse drug reactions, morbidity and mortality. The aim of this study was to determine the prevalence of potentially inappropriate medication in the older adult population attending primary care in Portugal and to identify associated sociodemographic and clinical factors. Methods: We conducted a cross-sectional, analytical study in primary care centres from the five Portuguese healthcare administrative regions and the two autonomous regions. We used a random sample of 757 older patients provided by the information department of the ministry of health (SPMS) and family doctors from the autonomous regions. Data collection occurred March 2018 and we studied sociodemographic characteristics, clinical profile and medication. We used 2015 Beers Criteria to assess potentially inappropriate medications. Logistic regression analyses were performed to determine associations between potentially inappropriate medications’ prescriptions and other variables. Results: Potentially inappropriate medication was present in 68.6% and 46.1% of the sample had two or more. The likelihood of having potentially inappropriate medication increased significantly with being female (OR=1.56 [1.05 to 2.31]), number of chronic health problems (OR=1.06 [1.01 to 1.13]), number of pharmacological subclasses (OR=1.40 [1.30 to 1.51]) and number of prescribers (OR=1.34 [1.09 to 1.65]). Proton-pump inhibitors, nonsteroidal anti-inflammatory drugs and benzodiazepines were the most commonly found ones. Conclusion: Potentially inappropriate medication in older adults was found to be a common occurrence in Portugal. It is important that doctors are aware of this problem, namely in the primary care setting due to the longitudinal care.